Dicarboxylato platinum(ii) complexes containing dimethyl sulfoxide and triazolopyrimidine as potential anticancer agents: synthesis, structural and biological studies in solution. (9th May 2018) - Jakubowski, Mateusz; Łakomska, Iwona; Sitkowski, Jerzy; Wiśniewska, Joanna
Abstract : N, O, S-donors platinum(ii ) complexes were synthesized and well characterized. We demonstrate that modification of coordination sphere by insertion of dmso molecule and bulky triazolopyrimidine ligand is good direction for the design effective less toxic platinum(ii ) complexes. Abstract : Four dicarboxylato platinum(ii ) complexes of the general formula [Pt(R(COO)2 )(dmso)(N-donor)], where: R(COO)2 – cyclobutane-1, 1-dicarboxylato or malonato, dmso – dimethyl sulfoxide and N-donor – 5, 7-dimethyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dmtp) or 5, 7-diphenyl-1, 2, 4-triazolo[1, 5- a ]pyrimidine (dptp), have been synthesized and structurally characterized using multinuclear magnetic resonance ( 1 H, 13 C, 15 N, and 195 Pt) techniques. The NMR parameters unambiguously confirmed the square-planar geometry of Pt(ii ) in solution with monodentate N(3)-bonded 5, 7-disubstituted-1, 2, 4-triazolo[1, 5- a ]pyrimidine, monodentate and S-bonded dimethyl sulfoxide and O, O-chelating dicarboxylate ions. The obtained platinum(ii ) complexes exhibit (i) higher susceptibility to hydrolysis and (ii) lower toxicity and affinity to glutathione in comparison with cisplatin and carboplatin. Additionally, it is noted that two lipophilic platinum(ii ) complexes: (3 ) [Pt(mal)(dmso)(dptp)] and (4 ) [Pt(CBDC)(dmso)(dptp)] display the most gratifying in vitro antiproliferative activity. Above and beyond, these promising coordination compounds exhibit definitely lower toxicity towards normal cells and anticancer activity comparable to that of cisplatin.